2017
DOI: 10.1111/eva.12536
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive evolution during the establishment of European avian‐like H1N1 influenza A virus in swine

Abstract: An H1N1 subtype influenza A virus with all eight gene segments derived from wild birds (including mallards), ducks and chickens, caused severe disease outbreaks in swine populations in Europe beginning in 1979 and successfully adapted to form the European avian‐like swine (EA‐swine) influenza lineage. Genes of the EA‐swine lineage that are clearly segregated from its closest avian relatives continue to circulate in swine populations globally and represent a unique opportunity to study the adaptive process of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…However, the isolation of a similar triple reassortant H1 av N2 virus in farm B in 2014, at the time the second reassortment event was estimated to have occurred, poses questions about where this event took place. Phylogenetic distances between the four studied strains were congruent, exhibiting genetic evolution rates similar to those reported for swIAV strains across years [23]. This argues in favor of the hypothesis that the triple reassortant strains originated from a single source rather than from two independent reassortment events, which would have resulted in two H1 av N2 triple reassortant strains exhibiting exactly the same gene constellation in the two distant farms.…”
Section: Discussionsupporting
confidence: 70%
“…However, the isolation of a similar triple reassortant H1 av N2 virus in farm B in 2014, at the time the second reassortment event was estimated to have occurred, poses questions about where this event took place. Phylogenetic distances between the four studied strains were congruent, exhibiting genetic evolution rates similar to those reported for swIAV strains across years [23]. This argues in favor of the hypothesis that the triple reassortant strains originated from a single source rather than from two independent reassortment events, which would have resulted in two H1 av N2 triple reassortant strains exhibiting exactly the same gene constellation in the two distant farms.…”
Section: Discussionsupporting
confidence: 70%
“…In a recent study reported by Joseph et al [51], the authors inferred that PB2-R251K played a critical role in the adaptation of avian influenza viruses into mammalian hosts by bioinformatics analysis. Of note, PB2 of the reassortant EA H1N1 virus (MS285 and YJ4 viruses) originates from the pdm/09 PB2 gene segment, implying that introduction of PB2-251K in pdm H1N1 virus may enhance its replication and pathogenicity in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The H1N1/2009 pandemic virus emerged from swine that contained gene segments ultimately derived from previously circulating human and avian viruses, highlighting a key role of segmental reassortment of genes from multiple hosts for host adaption and pandemic emergence. In this context, Joseph, Vijaykrishna, Smith, and Su () used a relaxed molecular clock model to test whether the European avian‐like swine (EA‐swine) influenza virus originated through the introduction of a single avian ancestor as an entire genome, followed by an analysis of host‐specific selection pressures among different gene segments. The results indicate independent introduction of gene segments via transmission of avian viruses into swine followed by reassortment events that occurred at least 1–4 years prior to the EA‐swine outbreak.…”
Section: Themes Of the Special Issuementioning
confidence: 99%
“…Complementing the work by Joseph et al., ; Grear, Hall, Dusek, and Ip () investigated mechanisms of intercontinental highly pathogenic avian influenza virus (HPAIV) spread through wild bird reservoirs possibly related to the North America outbreak in 2014. This introduction resulted in several reassortment events with North American (NA) lineage low‐pathogenic avian influenza viruses and the reassortant EA/NA H5N2 that went on to cause one of the largest HPAIV poultry outbreaks in North America.…”
Section: Themes Of the Special Issuementioning
confidence: 99%